Knowledge, attitude and behaviour towards the use of insecticide treated mosquito nets among pregnant women and children in rural Southwestern Uganda - Ivan M. Taremwa; Scholastic Ashaba; Harriet O. Adrama; Carlrona Ayebazibwe; Daniel Omoding; Imelda Kemeza; Jane Yatuha; Thadeus Turuho; Noni E. MacDonald; Robert Hilliard (BMC, 2017)
Abstract Background The burden of malaria in Uganda remains unacceptably high, especially among children and pregnant women. To prevent malaria related complications, household possession and use of Insecticide Treated mosquito Nets (ITNs) has become a common practice in the country. Despite the availability of ITNs, malaria remains a foremost public health concern in Uganda. We sought to explore knowledge, attitude, and behaviour towards the use of ITNs as a nightly malaria prevention strategy among pregnant women and children under five years of age in Isingiro district, Southwestern Uganda. Materials and Methods This was a community based, descriptive cross-sectional study, in which households with children under 5 years, and/or pregnant women were enrolled. We used a structured questionnaire to collect data on participants' understanding of the causes, signs and symptoms of malaria; use of ITNs to prevent malaria; attitudes and behaviours towards the use of ITNs. We also conducted key informant interviews (KIIs) to get in-depth understanding of responses from the participants. We analysed quantitative data using STATA version 12.Qualitative findings from the KIIs were transcribed and translated, and manually analysed using thematic content analysis. Results Of the 369 households enrolled, 98.4% (N = 363) households had children under five. Most participants (41.2%, N = 152) were in the 21-30 age category (mean age; 32.2 years). 98.1% (N = 362) of the respondents considered ITNs a key malaria prevention strategy. The ITN possession rate was 84.0% (N = 310), of these, 66.1% (N = 205) consistently used them. 39% of the respondents did not have a positive attitude towards ITNs. Conclusions Although 84.0% of the respondents possessed ITNs, many were not consistently using them. To this, there is need to engage all stakeholders (including cultural leaders, community health workers, religious leaders and the government) in the malaria prevention campaigns using ITNs through: a) government's concerted effort to ensure universal access of right fit ITNs, b) end-user directed health education to emphasize positive attributes of ITN use, c) telling the ITN success stories to improve on the usage.